Supply Chain Practice by Corporations through Transfer Pricing Mechanisms in Indonesia - Firmansyah, Amrie; Gunadi, Ariawan (ExcelingTech, 2020)
Abstract- This study aims to analyze legal certainty related to supply chain management on corporations that transfer pricing in transactions with related parties abroad and analyze corporate accountability for the practice of transfer pricing in the field of supply chain management in Indonesia. Transfer pricing carried out by multinational companies is an international world problem related to management strategy by diverting taxes to countries that have lower tax rates or countries that have a 0% tax rate. The research method used in this study by using a normative legal approach. The data used in this study uses primary legal materials and secondary legal materials. Primary legal documents are legal materials consisting of laws and regulations related to supply chain management in Indonesia and the OECD Guidelines. Meanwhile, secondary legal entities are materials that explain primary legal materials (legal science books, legal journals, print, and electronic media due to reports). Also, this study interviewed two informants who were experts in the field of international supply chain management and transfer pricing. This study concludes that the legislation in Indonesia is clear in regulating the implementation of transfer pricing carried out by multinational companies that have an impact on taxes collected by the Government of Indonesia. Supply chains are central to understanding wealth creation and capture in an increasingly globalized production system. The increasing disaggregation and dispersal of supply chains is profoundly affecting the geographical distribution of value added, input costs and profits of multinational firms.